Reasons of Request for Cone Beam Computed Tomography - Akleyin, Ebru; Eskibağlar, Mehmet (University of Dicle, 2022)
This retrospective study has aimed to examine the distribution of Cone Beam Computed Tomography (CBCT) request records in a dental faculty from 2011 to 2021 according to gender, diagnosis, the clinic making the request, and the year. In this study, archive records of 8214 CBCT images between January 2011 and January 2021 at Dicle University Faculty of Dentistry were examined. The findings showed that, in the last 10 years, the clinics requesting CBCT images were Oral, Dental, and Maxillofacial Surgery (48.6%), Orthodontics (20.4%), Oral, Dental and Maxillofacial Radiology (10.8%), Private Clinics (7.3%), Periodontology (4.3%), Pediatric Dentistry (2%) Endodontics (0.5%), and Restorative Dentistry (0.2%). CBCT was preferred for implant treatment planning (45.18%) and position of the embedded tooth (14.89%). In the evaluation made on CBCT request records of 8214 patients, 20 different reasons for request were identified. It was observed that CBCT images were mostly requested for implant treatment planning in the Oral, Dental and Maxillofacial Surgery clinic and CBCT requests were seen to increase from 2011 to 2021. © 2022, Journal of International Dental and Medical Research. All Rights Reserved.
Keywords: Cone beam computed tomography; Dentistry; Request reasons